Experimental study on the flexural strength of C-purlin sections - Go, Marc Arthur Z.
This paper aims to evaluate the flexural strength of cold-formed C-purlin sections through experimentation. Two (2) sets of C-purlin sections - 100 x 50 x 20 x 2.0 mm and 150 x 50 x 10 x 2.0 mm - were tested against uplift and downward loading using four-point loading system. The assembly comprised of a pair of C-purlin section with roof sheet fastened by tek screws. From the test, the failure modes of the purlins under different loading conditions were determined. For the downward loading, the design failure modes were consistent with the observed failure modes and concluded that the failure modes were not exclusive. This is supported in some of the test assemblies wherein both flange local buckling (FLB) and distortional buckling (DB) were observed. For the test assemblies exposed to uplift loading, significant deformation was observed due to the twisting of the whole section. Using the design provisions for cold-formed purlins from American Iron and Steel Institute (AISI), the theoretical capacity of the purlins was computed and was compared to the actual moment capacity obtained from testing. Three actual moment capacities were computed - actual yield, serviceability and ultimate capacity. The design capacity was compared to the actual yield and serviceability capacity. It was observed that the serviceability capacity is closer to the design capacity than the yield capacity.